2016
DOI: 10.1245/s10434-016-5282-4
|View full text |Cite
|
Sign up to set email alerts
|

LYMPHA Technique to Prevent Secondary Lower Limb Lymphedema

Abstract: The LYMPHA technique appears to be feasible, safe, and effective for the prevention of lower limb lymphedema, thereby improving the patient's quality of life and decreasing health care costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 24 publications
1
39
0
5
Order By: Relevance
“…Concerning the time to perform the anastomoses, the mean duration was comparable with those reported by Onda et al 13 (49.8 minutes vs 42.2 minutes; Table 1), but compared with LVA, even if the MLVA is ideally easier to perform, it presents some technical challenges such as the disparity of caliber between the lymphatics and the iliolumbar vein. In two cases over ten, indeed, after the insertion of the lymphatics, the right lumbar vein's diameter was reduced with an additional stitch.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Concerning the time to perform the anastomoses, the mean duration was comparable with those reported by Onda et al 13 (49.8 minutes vs 42.2 minutes; Table 1), but compared with LVA, even if the MLVA is ideally easier to perform, it presents some technical challenges such as the disparity of caliber between the lymphatics and the iliolumbar vein. In two cases over ten, indeed, after the insertion of the lymphatics, the right lumbar vein's diameter was reduced with an additional stitch.…”
Section: Discussionsupporting
confidence: 78%
“…This is the reason why over the last decades the rat has been a reliable training model to train residents in microsurgery. Yamamoto et al described a supermicrosurgical LVA model in rats performing the exercise on the hind limbs’ LVs, while Onoda et al reported an LVA model involving the use of lumbar lymphatic ducts and iliolumbar veins of rats …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As it was not in the scope of this systematic review, no conclusion can be made if LVA is effective and safe as a prevention treatment for secondary lymphoedema. Nevertheless, LVA may have a role in prevention of lymphoedema (Boccardo et al, 2016;Gomberawalla et al, 2017;Szolnoky, Dobozy, & Kemeny, 2014). Jorgensen et al performed a systematic review on the effect of prophylactic LVA and concluded that due to the heterogeneity between studies, the treatment could not be concluded effective and pointed out that there is a need for high quality studies on this topic (Jorgensen, Toyserkani, & Sorensen, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, researchers have reported that chronic lower extremity venous edema accompanied by varicose veins, lower extremity edema, and pain occurs only as a result of working in a standing posture for eight hours per day2 ) .…”
Section: Introductionmentioning
confidence: 99%